Direito à literatura e seus espaços de oferta - Reinol, Joyce Araujo [UNESP]; Souza, Renata Junqueira de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research has as pretension expatiate on the law to literature and the influence that the spaces where it is supplied causes in a person's life. Combining the right we all have access to literary works, is through the object book, or other spaces. Methodologically there was bibliographical study followed by application of story-telling and reading stories in different environments: the library of babies "Columns of knowledge" and the CELLIJ. For both, there was selection of history and the technique to be used, preparation of resources and space where happen the narrative. Thus, it was possible to observe and ratify what the readings and discussions in the presented: literature is essential for law humanization of children, since it can be implemented from the reflection of emotions or the sense of beauty. Everything that was observed in the watchful eyes and small participants feedback moments of literary reading in two spaces in question.

Esta pesquisa tem como pretensão discorrer sobre o direito à literatura e a influência que os espaços onde ela é ofertada ocasiona na vida de uma pessoa. Aliando ao direito que todos temos de acesso a obras literárias, seja por meio do objeto livro, ou demais espaços de ofertas. Metodologicamente houve estudo bibliográfico seguido de aplicação de contação e leitura de histórias em diferentes ambientes: a Bebeteca “Colunas do Saber” e o CELLIJ. Para tanto, houve seleção da história e da técnica a ser utilizada, preparação dos recursos e do espaço onde aconteceria a narrativa. Assim, foi possível observar e ratificar o que as leituras e discussões nos apresentaram: a literatura é direito indispensável à humanização das crianças, uma vez que ela pode ser concretizada a partir da reflexão, da harmonização das emoções ou do senso de beleza. Tudo que foi observado nos olhos atentos e comentários dos pequenos participantes dos momentos de leitura literária nos dois espaços em questão.
Keywords: Human rights; Literature; Offer spaces; Direitos; Literatura; Espaços de oferta